GLP-1 and calcitonin concentration in humans: lack of evidence of calcitonin release from sequential screening in over 5000 subjects with type 2 diabetes or nondiabetic obese subjects treated with the human GLP-1 analog, liraglutide - Hegedüs, Laszlo; Moses, Alan C; Zdravkovic, Milan; Le Thi, Tu; Daniels, Gilbert H (The journal of clinical endocrinology and metabolism, 2011)
Serum calcitonin (CT) is a well-accepted marker of C-cell proliferation, particularly in medullary thyroid carcinoma. Chronic glucagon-like peptide-1 (GLP-1) receptor agonist administration in rodents has been associated with increased serum CT levels and C-cell tumor formation. There are no longitudinal studies measuring CT in humans without medullary thyroid carcinoma or a family history of medullary thyroid carcinoma and no published studies on the effect of GLP-1 receptor agonists on human serum CT concentrations. The aim of the study was to determine serum CT response over time to the GLP-1 receptor agonist liraglutide in subjects with type 2 diabetes mellitus or nondiabetic obese subjects. Unstimulated serum CT concentrations were measured at 3-month intervals for no more than 2 yr in a series of trials in over 5000 subjects receiving liraglutide or control therapy. Basal mean CT concentrations were at the low end of normal range in all treatment groups and remained low throughout the trials. At 2 yr, estimated geometric mean values were no greater than 1.0 ng/liter, well below upper normal ranges for males and females. Proportions of subjects whose CT levels increased above a clinically relevant cutoff of 20 ng/liter were very low in all groups. There was no consistent dose or time-dependent relationship and no consistent difference between treatment groups. These data do not support an effect of GLP-1 receptor activation on serum CT levels in humans and suggest that findings previously reported in rodents may not apply to humans. However, the long-term consequences of GLP-1 receptor agonist treatment are a subject of further studies.